Разработка концепции эффективного управления в туристической отрасли. - Падерин, А.В. (Культура народов Причерноморья, 2013)
It is suggested in the article to promote the efficiency of tourist industry functioning, based on the opportunities, given by management. Thus the instrument of management realization is conception. This document comes forward as a set of measures, directed on achievement of functioning and development of tourism sphere efficiency in accordance with the management paradigm, folded in industry. The conception feature is a high degree generalization of flowings processes in the field of tourism. It is done from the concrete practical steps on efficiency achievement. The special place to co-operation of the state and business is depicted in the conception. The features of management realization on macro- and microlevel in the field of tourism are reflected in the document for this purpose. These features are designed as the management model on macro- and microlevel in the end. The centralized model, in which a major place is taken to a public policy in tourism sphere, carried out at close co-operation of the state and business, is designed on a macrolevel. The management model of a joint-stock company is suggested in tourism sphere on a microlevel. The co-operation between macro- and microlevel is described by an organizational-economic mechanism.